Capillary electrophoresis for the analysis of paralytic shellfish poisoning toxins in shellfish: Comparison of detection methods. Issue 10 (13th April 2014) - Keyon, Aemi S. Abdul; Guijt, Rosanne M.; Gaspar, Andras; Kazarian, Artaches A.; Nesterenko, Pavel N.; Bolch, Christopher J.; Breadmore, Michael C.
<x xml:space="preserve">Abstract</x> Paralytic shellfish toxins (PSTs) are produced by marine and freshwater microalgae and accumulate in shellfish including mussels, oysters, and scallops, causing possible fatalities when inadvertently consumed. Monitoring of PST content of shellfish is therefore important for food safety, with currently approved methods based on HPLC, using pre‐ or postcolumn oxidation for fluorescence detection (HPLC‐FLD). CE is an attractive alternative for screening and detection of PSTs as it is compatible with miniaturization and could be implemented in portable instrumentation for on‐site monitoring. In this study, CE methods were developed for C4D, FLD, UV absorption detection, and MS—making this first report of C4D and FLD for PSTs detection. Because most oxidized toxins are neutral, MEKC was used in combination with FLD. The developed CZE‐UV and CZE‐C4D methods provide better resolution, selectivity, and separation efficiency compared to CZE‐MS and MEKC‐FLD. The sensitivity of the CZE‐C4D and MEKC‐FLD methods was superior to UV and MS, with LOD values ranging from 140 to 715 ng/mL for CZE‐C4D and 60.9 to 104 ng/mL for MEKC‐FLD. With the regulatory limit for shellfish samples of 800 ng/mL, the CZE‐C4D and MEKC‐FLD methods were evaluated for the screening and detection of PSTs in shellfish samples. While the CZE‐C4D method suffered from significant interferences from the shellfish matrix, MEKC‐FLD was successfully used for PST screening of a periodate‐oxidized mussel sample, with results confirmed by HPLC‐FLD. This confirms the potential of MEKC‐FLD for screening of PSTs in shellfish samples.